Ataque de Trigona spinipes (Fabr.) (Hymenoptera: Apidae: Meliponinae) em pitaia Hylocereus undatus (Haw.) e Hylocereus polyrhizus (Weber) (Cactaceae) em Couto de Magalhães de Minas, Minas Gerais, Brasil - Alves, Deilson de Almeida; Lima, João Esdras; Soares, Marcus Alvarenga; Rabelo, Josimara Mendes; da Cruz, Maria do Céu Monteiro (EntomoBrasilis, 2018)
Resumo. A pitaia Hylocereus spp. (Cactaceae) é uma espécie frutífera exótica com cultivo em fase de expansão no Brasil. Problemas com pragas ainda são poucos relatados. Com isso, o objetivo deste trabalho foi relatar a ocorrência da abelha arapuá Trigona spinipes (Fabr.)(Hymenoptera: Apidae) em espécies de pitaia Hylocereus undatus (Haw.) e Hylocereus polyrhizus (Weber) no município de Couto de Magalhães de Minas, Minas Gerais, Brasil. Os danos principais decorrentes do ataque ocorrem nos frutos maduros, depreciando o fruto para comercialização. Este registro demonstra que T. spinipes necessita ser monitorada pelo potencial causador de danos significativos em pitaia e consequentemente perdas na produção. Attack of Trigona spinipes (Fabr.) (Hymenoptera: Apidae: Meliponinae) in dragon fruit Hylocereus undatus (Haw.) and Hylocereus polyrhizus (Weber) (Cactaceae) in Couto de Magalhães de Minas, Minas Gerais State, Brazil Abstract. The dragon fruit Hylocereus spp. (Cactaceae) is an exotic fruit species with crop in expansion phase in Brazil. Problems with pests are still few reported. The objective of this work was to report the occurrence of the Trigona spinipes (Fabr.) (Hymenoptera: Apidae) bee on the dragon fruit species Hylocereus undatus (Haw.) and Hylocereus polyrhizus (Weber) in the municipality of Couto de Magalhães de Minas, Minas Gerais State, Brazil. The main damages resulting from the attack occur in the mature fruits, depreciating them for commercialization. This record demonstrates that T. spinipes needs to be monitored for the potential to damage dragon fruit and consequently production losses.